THE EFFECT OF K-W-L TEACHING TECHNIQUE ON THE READING COMPREHENSION ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 12 PEKANBARU - Widi, Rahma; Gultom, Effendy; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental study is aimed at finding out if there is a significant effect of Know, Want to know, and Learned (KWL) teaching techniqueon the ability of the first year students of SMAN 12 Pekanbaru in comprehending report texts. The design of the study is one group pre-test-treatment-posttest design. There are 12 classes in the first year. As many as 36 students of class X IPS 3 in the first semester of academic year 2018/2019 are chosen as the sample by using cluster random sampling technique due to the particular class presents various characters of the whole classes like; academic achievement, the students’ learning seriousness toward English and the size of the classroom. The instrument of the test is in the form of multiple choice which consist of 25 items about report texts. To collect the needed data the treatments were conducted for six times. The students’ scores were analyzed by using SPSS (Statistical Package for the Social Sciences) version 23.00 for windows. The results of the data analysis show that the mean score of the pre-test is 57.556 and the mean score of the post-test is 79.00. It means that the value of t-test is higher than t-table (11.055>1.95996) at 5% the significance level. Therefore, the alternative hyphotesis (H1) of this study is accepted. In other words, there is a significant effect of KWL teaching technique on the reading comprehensionability of the first year students of SMAN 12 Pekanbaru. The implication of this finding is be beneficial for the teachers in teaching and learning English especially in teaching reading.Keywords: Effect, KWL Teaching Technique, Reading Comprehension